PENGARUH PENGGUNAAN BUSI STANDAR DAN BUSI IRIDIUM TERHADAP KONSUMSI BAHAN BAKAR PADA TOYOTA KIJANG 7K EFI - Syamsuddin, Usman; sukri, Sukri (ELEMEN : JURNAL TEKNIK MESIN, 2025)
Spark plugs are an important component in the combustion process in the combustion chamber. The type of spark plug used will affect fuel consumption. This study aims to determine the comparison of fuel consumption when using iridium spark plugs and standard spark plugs. The method used is to test on 3 variations of engine rotation, namely 1000, 1500 and 2000 rpm with a duration of 5 minutes. The results of the study show that the average fuel consumption when using iridium spark plugs is greater than that of standard spark plugs. The average fuel consumption using an iridium spark plug at 1000 rpm is 33 mL more wasteful than using a standard spark plug, at 1500 rpm the engine speed is 27 mL more wasteful and at 2000 rpm the engine is more wasteful by 10 mL. So it can be concluded that the use of iridium spark plugs in 3 variations of engine rotation is 20.14% more wasteful than using standard spark plugs.